2020
DOI: 10.1111/apa.15489
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis suggest that the duration of Kangaroo mother care has a direct impact on neonatal growth

Abstract: Aim: A 2016 Cochrane review showed that Kangaroo mother care (KMC) had a moderate impact on preterm growth, with high heterogeneity among studies. This systematic review and meta-analysis considered new evidence on KMC, particularly the duration. Method: Databases were searched for papers published in English, French, Spanish and Portuguese up to 2017. Randomised controlled trials (RCT) of preterm or low birth weight infants were included if they compared growth between KMC and conventional care. Anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 39 publications
2
32
2
1
Order By: Relevance
“…Finally, there was a lack of evidence on support for women with preterm infants. As additional considerations are needed for preterm infants, for example kangaroo care (Charpak et al, 2021) responsive versus scheduled feeding (Watson & McGuire, 2016), the use of milk banks (Quigley et al, 2019), use of bottles or cups (Collins et al, 2016), and therefore the evidence from studies with term babies may not be applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there was a lack of evidence on support for women with preterm infants. As additional considerations are needed for preterm infants, for example kangaroo care (Charpak et al, 2021) responsive versus scheduled feeding (Watson & McGuire, 2016), the use of milk banks (Quigley et al, 2019), use of bottles or cups (Collins et al, 2016), and therefore the evidence from studies with term babies may not be applicable.…”
Section: Discussionmentioning
confidence: 99%
“…It is apparent that demotivated health care providers' and caregivers" reluctance seriously impedes the implementation of KMC in Bangladesh, as observed in other low-income countries, namely Vietnam, Malawi, Uganda, and Mali [14,17,30,35], which affected the fidelity of KMC. Across all health facilities visited, the prevailing health system challenges were inadequate and skilled human resources and excessive workload.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have clear implications for the Brazilian public health care setting, which is primarily guided by low birthweight and prematurity guidelines to determine eligibility for primary care interventions. For example, the 'kangaroo method', 30 a public health intervention aiming to increase the physical contact of mothers with their lowbirthweight newborn babies, might benefit from twinspecific guidelines that also considers sex differences in mortality. Increased birthweight for males compared with their female co-twins, on average, did not confer any protection from infant mortality.…”
Section: Discussionmentioning
confidence: 99%
“…2 Males are at higher risk than females for neonatal morbidity and mortality despite being heavier at birth. 3 This disadvantage is more evident for newborns with lower birthweight, as evidenced by a study in the USA which found that 22% [95% confidence interval (CI): [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] of boys and 15% (95% CI: 11-22) of girls who weighed less than 1500 g at birth died before hospital discharge. 4 Studying sex differences in early life mortality is challenging, not least because birthweight and gestational age, which are likely to be potential confounders or mediators, are familial and correlated with each other.…”
Section: Introductionmentioning
confidence: 99%